Being Indigenous in Jim Crow Virginia - Feller, Laura J. (University of Oklahoma Press, 2022)
Virginia’s Racial Integrity Act of 1924 recodified the state’s long-standing racial hierarchy as a more rigid Black-white binary. Then, Virginia officials asserted that no Virginia Indians could be other than legally Black, given centuries of love and marriage across color lines. How indigenous peoples of Virginia resisted erasure and built their identities as Native Americans is the powerful story this book tells. Spanning a century of fraught history, Being Indigenous in Jim Crow Virginia describes the critical strategic work that tidewater Virginia Indians, descendants of the seventeenth-century Algonquian Powhatan chiefdom, undertook to sustain their Native identity in the face of deep racial hostility from segregationist officials, politicians, and institutions.